Curcumin Supplementation (Meriva®) Modulates Inflammation, Lipid Peroxidation and Gut Microbiota Composition in Chronic Kidney Disease - Pivari, Francesca; Mingione, Alessandra; Piazzini, Giada; Ceccarani, Camilla; Ottaviano, Emerenziana; Brasacchio, Caterina; Dei Cas, Michele; Vischi, Margherita; Cozzolino, Mario Gennaro; Fogagnolo, Paolo; Riva, Antonella; Petrangolini, Giovanna; et al. (Nutrients, 2022)
Chronic kidney disease (CKD) subjects suffer from high risk of cardiovascular mortality, and any intervention preventing the progression of CKD may have an enormous impact on public health. In the last decade, there has been growing awareness that the gut microbiota (GM) can play a pivotal role in controlling the pathogenesis of systemic inflammatory state and CKD progression. To ameliorate the quality of life in CKD subjects, the use of dietary supplements has increased over time. Among those, curcumin has demonstrated significant in vitro anti-inflammatory properties. In this pilot study, 24 CKD patients and 20 healthy volunteers were recruited. CKD patients followed nutritional counselling and were supplemented with curcumin (Meriva®) for six months. Different parameters were evaluated at baseline and after 3–6 months: uremic toxins, metagenomic of GM, and nutritional, inflammatory, and oxidative status. Curcumin significantly reduced plasma pro-inflammatory mediators (CCL-2, IFN-γ, and IL-4) and lipid peroxidation. Regarding GM, after 6 months of curcumin supplementation, Escherichia-Shigella was significantly lower, while Lachnoclostridium was significant higher. Notably, at family level, Lactobacillaceae spp. were found significantly higher in the last 3 months of supplementation. No adverse events were observed in the supplemented group, confirming the good safety profile of curcumin phytosome after long-term administration.